1999
DOI: 10.1063/1.478448
|View full text |Cite
|
Sign up to set email alerts
|

Predicting nonstatistical unimolecular reaction rates using Kramers’ theory

Abstract: Articles you may be interested inOn the role of coherence in the transition from kinetics to dynamics: Theory and application to femtosecond unimolecular reactions A theory for nonisothermal unimolecular reaction rates Response to "Comment on 'On the relation between unimolecular reaction rates and overlapping resonances'" [A method for computing unimolecular reaction rate constants in the IVR-limited regime is presented. It is based on Kramers' energy diffusion theory, with the reaction coordinate taken as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The present approach enables us to extend our previous studies [10][11][12][13][14] of IVR-controlled reactions to the more general case whether the rate of IVR is faster or slower than the rate of reaction. Assuming constant friction, the method predicts the rate constants for a wide range of energies by requiring only one rate from a trajectory calculation at a single energy to determine the friction coefficient.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The present approach enables us to extend our previous studies [10][11][12][13][14] of IVR-controlled reactions to the more general case whether the rate of IVR is faster or slower than the rate of reaction. Assuming constant friction, the method predicts the rate constants for a wide range of energies by requiring only one rate from a trajectory calculation at a single energy to determine the friction coefficient.…”
Section: Discussionmentioning
confidence: 96%
“…16 We have applied the energy diffusion theory to compute the microcanonical rates for large molecules in the high-energy (diffusion) regime by assuming that the IVR rate is much slower and thus determines the dynamic rate. [11][12][13][14] The present approach enables us to obtain the reaction rates more generally for the entire range of energies from the statistical to the diffusion limit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…͑4͒ is the energy diffusion coefficient D(E). As in our previous study, 7 we use Kramers' result 8,17 for a onedimensional particle interacting with a heat bath. Assuming constant friction, Kramers showed that the energy diffusion coefficient is…”
Section: Energy Diffusion Theory For Unimolecular Reactionsmentioning
confidence: 99%
“…7 We applied the method to two bondfission reactions. The calculated rates from the IDDT are in good agreement with those from trajectory simulations, showing that the method is accurate for computing the unimolecular reaction rates.…”
Section: Introductionmentioning
confidence: 99%